¿Petronio en la biblioteca de San Isidoro de Sevilla? - Rodríguez Morales, Jesús (Antigüedad y Cristianismo, 1990)
The author begins his study with an appraisal of the quotations from the Satyricon which appear in the Etymologiae of S. Isidore and later reviews the sources of the Isidorian worlis. He likewise studies the characteristics of the way the Sevillian worked and his poor critical capacity. The article centers on the significance of the works of Petronius and reaches the conclusion that the Saint must have had in his hands a complete copy of the work because his manner of citing seems to exclude the possibility of having used a florilegium. The author thinks that it’s very probable that the copy Isidore had, must have been much more extensive than that which we have today.